KERUKUNAN DALAM PERBEDAAN: PEMAKNAAN JAMAAH TERHADAP KEHADIRAN TIGA IMAM DI MASJID BELANG-BELANG - Syahru Ramadhan A; Laela Safriani; Musyawir Muwafiq; Rizfa Aulia; Abd. Rahman (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This research originates from the discourse of the sociology of religion and Islamic studies, which highlight the dynamics of religiosity in the context of fiqh diversity and worship practices in Indonesia. The phenomenon of three imams at Belang-Belang Mosque is interesting to examine because it reflects tolerance and moderation in the religious life of the community. The purpose of this study is to understand the congregation's meaning of the presence of three imams and to find solutions to maintain social-religious harmony amidst differences. This study uses a phenomenological qualitative approach with in-depth interviews, participatory observation, and documentation techniques. Analysis is conducted using the Miles and Huberman interactive model. The research results show that the presence of three imams does not cause division, but becomes a symbol of harmony in diversity. The congregation is able to manage differences in fiqh views through the values of ukhuwah islamiyah (brotherhood) and tasamuh (tolerance). This phenomenon demonstrates the practical application of Islamic Nusantara that balances individual piety with social harmony. Theoretically, this research contributes to strengthening the concept of religious moderation in Islamic sociology. Practically, the results can serve as a model for managing congregational harmony amid differences in schools of thought and worship traditions.